2020
DOI: 10.1136/neurintsurg-2019-015754
|View full text |Cite
|
Sign up to set email alerts
|

Robotic assisted carotid artery stenting for the treatment of symptomatic carotid disease: technical feasibility and preliminary results

Abstract: Background and purposeRobotic-assisted endovascular interventions have been increasingly performed in the coronary and peripheral vascular beds. We aim to describe the feasibility and initial safety of a robotic-assisted platform for treating carotid artery disease.MethodsSingle-center technical report of the first four consecutive cases of carotid artery stenting for the treatment of severe symptomatic carotid stenosis utilizing the CorPath GRX Robotic System (Corindus Inc, Waltham, MA).ResultsFour patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 11 publications
0
48
0
Order By: Relevance
“…Closely related to this topic is the introduction of robotics into the neurointerventional routine. To date, few groups have reported small case series of successful robot-assisted elective procedures [31][32][33], and first attempts are being made to create ethical and medicolegal frameworks [34] for neurointerventional robotics. The degree of autonomy of current robotic systems is however very low and their utility restricted by the incapability of performing essential tasks, such as puncturing the groin.…”
Section: Desirable Developments We Should Aim For In the Near Futurementioning
confidence: 99%
“…Closely related to this topic is the introduction of robotics into the neurointerventional routine. To date, few groups have reported small case series of successful robot-assisted elective procedures [31][32][33], and first attempts are being made to create ethical and medicolegal frameworks [34] for neurointerventional robotics. The degree of autonomy of current robotic systems is however very low and their utility restricted by the incapability of performing essential tasks, such as puncturing the groin.…”
Section: Desirable Developments We Should Aim For In the Near Futurementioning
confidence: 99%
“…Furthermore, transradial carotid artery stenting has demonstrated feasibility and safety in CAS[ 30 - 32 ]. Recently, robotic-assisted CAS has been shown to be technically feasible; however, further studies are warranted to properly establish the safety and benefits of this technique[ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar research group conducted a retrospective comparison of transradial robot-assisted carotid stent placement with manual stent placement and found that the mean procedural duration was significantly longer while using the robot (85.0 [SD, 14.3] versus 61.2 [SD, 17.5] minutes), but there was no significant difference in other procedural characteristics such as fluoroscopy time, contrast dose, radiation exposure, catheter exchanges, technical success, transfemoral conversion, and complications. 54 Nogueira et al 55 also recently treated 4 patients with severe symptomatic carotid stenosis and achieved technical and procedural success. All steps of the procedure were completed by the robotic system except for navigation and deployment of the stent, which is currently incompatible.…”
Section: Clinical Applications Of Robotic Neurointerventionmentioning
confidence: 99%